Endovascular therapy for anterior circulation large vessel occlusion in telestroke. (April 2021) - Moustafa, Haidar; Barlinn, Kristian; Prakapenia, Alexandra; Winzer, Simon; Gerber, Johannes; Pallesen, Lars-Peder; Siepmann, Timo; Haedrich, Kevin; Wojciechowski, Claudia; Reichmann, Heinz; Linn, Jennifer; Puetz, Volker; et al.
Introduction: Recent exploratory analysis suggested comparable outcomes among stroke patients undergoing endovascular therapy (EVT) for anterior circulation large vessel occlusion, whether selected via the telestroke network or admitted directly to an EVT-capable centre. We further studied the role of telemedicine in selection of ischaemic stroke patients potentially eligible for EVT. Methods: We prospectively included consecutive ischaemic stroke patients with anterior circulation large vessel occlusion who underwent EVT at our neurovascular centre (January 2016 to March 2018). We compared safety and efficacy including symptomatic intracerebral haemorrhage (sICH), successful reperfusion (mTICI 2b/3), 90-day favourable outcome (mRS ≤ 2) and 90-day survival between patients transferred from telestroke hospitals and patients directly admitted. Results: Of 280 potentially EVT-eligible patients, 72/129 (56%) telestroke and 91/151 (60%) direct admissions eventually underwent EVT (age 76 (66–82) years, median (interquartile range), 46% men, NIHSS score 17 (13–20)). Telestroke patients had larger pre-EVT infarct cores (ASPECTS: 7 (6–8) vs . 8 (7–9); p  < 0.0001) and shorter door-to-groin puncture times (71 (56–84) vs . 101 (79–133) min; p  < 0.0001) than directly admitted patients. sICH (2.8% vs . 1.1%; p  = 0.58), successful reperfusion (81% vs . 77%; p  = 0.56), 90-day favourable outcome (25% vs . 29%; p  = 0.65) and 90-day survival (73% vs . 67%; p  = 0.39) rates were comparable among telestroke and direct admissions. Discussion: Our data underpins the important role of telemedicine in identifying acute ischaemic stroke patients lacking immediate access to EVT-capable stroke centres. Stroke patients selected via telemedicine and those directly admitted had comparable chances of favourable outcomes after EVT for large vessel occlusion.